Participation of Citizen as Social Capital in LAPOR! Application in Indonesia - Febriani, Rika; Luthfi, Zaky Farid; Waldi, Atri (Society of Visual Informatics, 2024)
Citizen engagement is crucial for the success of smart cities. In urban areas, communities as social capital has an interpersonal bond that unites people. Due to the complexity of urban issues like pollution, waste, and population density, citizens can monitor the government's work priorities to solve the problem. This article focuses on smart cities from a human-centered perspective, emphasizing the role of information technology. In Indonesia, citizens' rights awareness is facilitated by the National Public Service Complaint Management System (SP4N) or People's Aspiration and Online Complaints Service (LAPOR!), which acts as social capital. This article explores five key aspects of smart cities and smart citizenship: governance, citizen participation, infrastructure, public spaces, and urban livability. While ICT-driven approaches can swiftly transform cities, a community-based approach fosters long-term shifts. Meanwhile, limited citizen involvement contributes to ecosystem degradation in Indonesia and underscores the urgency and importance of citizen engagement in urban planning. In democratic societies, citizens hold power, and concepts of smart citizenship encompass civic intelligence and, at the same time, also value local knowledge. In Indonesia, LAPOR! reflects smart citizenship, enabling transparent reporting of aspirations and complaints. However, factors like limited access and education of citizens affect its use. This research used qualitative methods with content analysis methods. Qualitative content analysis is used to examine the textual content of websites. Using LAPOR! SP4N in Indonesia to see the implementation of the concept of smart society and smart city. Participatory processes should contribute substantially to urban planning and governance. Information technology serves as a temporary solution for long-term urban planning issues. Broader concerns like public policy and participatory democracy must also be considered. In conclusion, this article explores the dynamic relationship between smart cities and smart citizenship, highlighting the importance of active citizen engagement and the potential of technology to empower communities for positive urban transformations.